PENERAPAN MODEL FLIPPED CLASSROOM DALAM PEMBELAJARAN MENUIS CERPEN PADA SISWA KELAS XI SMK PUI GEGESIK - Afiyah Sulthanah Khayyirah; Irfan Efendi; Ade Hasanudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is entitled "The Implementation of the Flipped Classroom Model in Teaching Short Story Writing to Grade XI Students of SMK PUI Gegesik." The subjects of this study were students from Grade XI at SMK PUI Gegesik, with class XI TAV 2 as the experimental group and class XI TAV 1 as the control group. The study was motivated by the low average student scores that did not meet the Learning Mastery Criteria (KKTP), the limited variation in teaching models used, the lack of active classroom engagement, and the students’ limited understanding of short story structure. The objectives of this research were to determine the effectiveness and the learning activity levels in short story writing using the flipped classroom model. The research method was an experimental study, with data collected through pretests, posttests, and observation. Statistical analysis using an independent samples t-test showed that the t-value (3.217) was greater than the t-table value (2.002), indicating a significant difference between the experimental and control groups. Thus, it can be concluded that the flipped classroom model is effective in teaching short story writing. Moreover, observation results indicated that both teacher and student activities were in the “good” category, with scores of 85 and 83 respectively, reflecting increased student engagement during the learning process.